2015
DOI: 10.1111/opo.12225
|View full text |Cite|
|
Sign up to set email alerts
|

The short‐term accommodation response to aniso‐accommodative stimuli in isometropia

Abstract: The dominant and non-dominant eyes of young isometropic individuals display a similar consensual lag of accommodation under both monocular and binocular viewing conditions, with the dominant eye showing a small but significantly greater (by 0.12-0.25 D) accommodative response. Evidence of short-term aniso-accommodation in response to asymmetric accommodation demands was not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…There were several limitations to our study. First, for the same subject, we performed different methods on different eyes because of the physical constraints of our Badal system mounted on the Grand Seiko, which might have caused bias in our study; however, Vincent and colleagues reported that young subjects with minimal anisometropia and astigmatism, which describes the sample in this study, exhibited very small differences in the accommodation response between fellow eyes for a range of viewing conditions assessed with an open‐field autorefractor. Second, the non‐randomisation of the order of the three methods may have led to a fatigue effect in the results and consequently the lower AA measured with the minus lens technique compared to Anderson and colleagues .…”
Section: Discussionmentioning
confidence: 99%
“…There were several limitations to our study. First, for the same subject, we performed different methods on different eyes because of the physical constraints of our Badal system mounted on the Grand Seiko, which might have caused bias in our study; however, Vincent and colleagues reported that young subjects with minimal anisometropia and astigmatism, which describes the sample in this study, exhibited very small differences in the accommodation response between fellow eyes for a range of viewing conditions assessed with an open‐field autorefractor. Second, the non‐randomisation of the order of the three methods may have led to a fatigue effect in the results and consequently the lower AA measured with the minus lens technique compared to Anderson and colleagues .…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence regarding the impact of uncorrected anisometropia on children's performances in school. Although some studies have investigated the visual deficits associated with amblyopic anisometropia, few have explored functional deficits associated with non‐amblyopic anisometropia, which can potentially disrupt binocular co‐ordination due to interocular differences in accommodative demand, or retinal image size . This may result in visual symptoms such as headaches and eyestrain, which can contribute to a reduction in functional performance .…”
Section: Vision Refractive Error and Academic Performancementioning
confidence: 99%
“…Ocular dominance plays an important role in reading [ 10 ]. Vincent et al [ 11 ] found that the dominant eye is showing significantly greater accommodative response during binocular viewing. Based on the assumption that blur is easier to be suppressed in nondominant eye, dominant eye is usually corrected for distant vision and nondominant eye is usually corrected for near vision in monovision design.…”
Section: Introductionmentioning
confidence: 99%